2018
DOI: 10.3390/w10121764
|View full text |Cite
|
Sign up to set email alerts
|

Biostability of Tap Water—A Qualitative Analysis of Health Risk in the Example of Groundwater Treatment (Semi-Technical Scale)

Abstract: This article presents results of research which aimed to assess the impact of biofiltration processing on the biological stability of water. Effectiveness of biogenic substances removal (C, N, P) and bacteriological quality of water after the biofiltration process were discussed. The research was carried out on a semi-technical scale on natural underground water rich in organic compounds. A filter with a biologically active carbon (BAC) bed was used for the research. Despite the low water temperature of betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Thus, biostable water does not contain microorganisms and does not support their development in the storage tank. The instability of water, resulting in the development of biofilm on the internal surfaces of the storage tank and installation pipes, low organoleptic properties of water and secondary contamination with pathogenic bacteria [42].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, biostable water does not contain microorganisms and does not support their development in the storage tank. The instability of water, resulting in the development of biofilm on the internal surfaces of the storage tank and installation pipes, low organoleptic properties of water and secondary contamination with pathogenic bacteria [42].…”
Section: Discussionmentioning
confidence: 99%
“…Biological stability of water is conditioned by both the content of organic and non-organic substances. For instance, nitrogen, phosphorus, and organic substrates may create conditions for the growth of heterotrophic organisms, including pathogenic microorganisms in the DWDS [37][38][39]. It has also been shown that trace metals such as iron and copper can affect biofilm development in DWDS [40][41][42].…”
Section: Impact Of Biofilms On Water Quality and Biostabilitymentioning
confidence: 99%
“…The biological stability of water is conditioned by the content of inorganic nutrients, i.e., nitrogen and phosphorus, which are necessary for the development of all forms of microorganisms, and the content of organic food substrates, creating conditions for the growth of heterotrophs and pathogenic microorganisms [42,43].…”
Section: Parameters Characterizing the Biological And Chemical Stabilmentioning
confidence: 99%